CONTROL SYSTEMS AND GOAL ORIENTATION IN ECO-DESIGN PERFORMANCE - Khansa Adira Paradis; Dyah Ekaari Sekar Jatiningsih (Widya Mandala Surabaya Catholic University, 2026)
Research Purposes. This study aims to examine how Management Control Systems (MCS), Learning Orientation (LO), and Performance-Prove Orientation (PPO) influence eco-friendly design performance, and whether their alignment improves sustainability-focused outcomes. Research Methods. This study used a quantitative 2×2×2 experimental design with a LEGO-based eco-design task involving 171 accounting students. Participants were assigned to Diagnostic or Interactive MCS conditions and exposed to priming scenarios for Learning Orientation (LO) and Performance-Prove Orientation (PPO). Data were analysed using ANOVA (SPSS). Research Results and Findings. The results show no significant main effects for MCS, LO, or PPO individually. However, a significant three-way interaction was found. Eco-design performance was highest when Interactive MCS aligned with low LO and low PPO, and when Diagnostic MCS aligned with high LO and low PPO. When PPO was high, differences between conditions became minimal. This study contributes to the behavioural accounting literature and managerial practice by highlighting the importance of aligning management control systems with individual goal orientations to support eco-design.